ANALYSIS RATIO LIQUIDITY AND PROFITABILITY PT. KIMIA FARMA (PERSERO) TBK - Putri, Ayu Mardiah; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The purpose of this study was to analyze the liquidity ratio and profitability ratio at PT. Kimia Farma (Persero) Tbk from 2014-2018, namely by using financial analysis based on liquidity ratios and profitability ratios. Financial ratios to answer questions about the company's financial health, including the company's liquidity and profitability, which describes the company's ability to meet its short-term obligations and the company's ability to generate profits from the use of company assets. In this study the authors used primary and secondary data sources. While the data analysis method used is descriptive quantitative method, namely research by describing (describing) and explaining about a financial report issued by PT. Kimia Farma (Persero) Tbk. The results showed that the company's liquidity ratio is already good, where the liquidity ratio has shown the company's ability to meet its short-term obligations is very large and the profitability ratio is not good because the company has a profitability that is below standard. Keywords: Financial Statements, Liquidity Ratios, Profitability Ratios.